Comparative Gut Microbiomes of Four Species Representing the Higher and the Lower Termites. Issue 1 (25th August 2016) - Su, LiJuan; Yang, LeLe; Huang, Shi; Su, XiaoQuan; Li, Yan; Wang, FengQin; Wang, EnTao; Kang, Ning; Xu, Jian; Song, AnDong
Abstract: Aiming at learning the association between the gut microbiota and termites with different diet habits and phylogenetic positions, the gut bacteria of three populations for each of the two higher termites (wood-feeding Mironasutitermes shangchengensis and fungus-feeding Odontotermes formosanus ) and two wood-feeding lower termites ( Tsaitermes ampliceps and Reticulitermes flaviceps ) were analyzed by high-throughput 454 pyrosequencing of 16S V1–V3 amplicons. As results, 132 bacterial genera and some unidentified operational taxonomic units within 29 phyla in the gut bacteria were detected, with Spirochaetes (11–55%), Firmicutes (7–18%), Bacteroidetes (7–31%), and Proteobacteria (8–14%) as the main phyla, and Treponema, TG5, Dysgonomonas, Tannerella, za29, Lactococcus, Pseudomonas, and SJA-88 as the common genera in all the four termites. The diversity of gut bacterial communities in the higher termite guts was significantly greater than that in the lower termites; while the gut microbiota in M. shangchengensis (wood-feeding higher termite) was more similar to those of the wood-feeding lower termites rather than that of O. formosanus (fungus-feeding higher termite), and phylum Spirochaetes and nitrogen-fixing bacteria were super-dominant in the wood-feeding termites, despite of their phylogenetic relations. This study reported for the first time the gut bacterial communities for the termites of M. shangchengensis and T. ampliceps and the comparative analyses showed that the gut microbial communities varied according to the phylogeny and the diet habits of termites.